A MODERN APPROACH TO THE REGULATION OF CRIMINAL LIABILITY FOR ILLEGAL EXTRACTION OF AQUATIC BIOLOGICAL RESOURCES UNDER THE LEGISLATION OF THE CIS COUNTRIES - Nurutdinova, Айнур Жарылғасынқызы; Tleulessova, Багила Тлеулесовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2024)
The scientific work examines some issues of legal regulation of the protection and use of aquatic biological resources. The work examines and analyzes the legislative experience of some CIS member states, including those belonging to the Caspian states. The presence of the latter is explained by the need for joint cooperation between States to combat illegal fishing of fish and other aquatic biological resources and preserve biological diversity. The article substantiates the question of the possibilities of developing the institution of legal responsibility for the illegal extraction of aquatic representatives of flora and fauna. In addition, the provisions of the articles of the criminal legislation of the CIS countries, which were influenced by the legislation of the Soviet Union, are considered. On this basis, the general distinctive features of the provisions on the application of criminal liability for non-compliance with legislation in relation to aquatic biological resources are identified. In addition, the peculiarities in the regulation of the studied legal relations by individual states are determined in terms of establishing the subject of the crime, qualifying signs of the corpus delicti, and the amount of damage to the environment. In addition, the paper raises the issue of international cooperation between countries regarding the protection and rational use of aquatic biological resources. In this regard, the most effective are the joint organizational actions of the States, which can be reflected in the Protocol on Cooperation currently under discussion in the Field of Combating Illegal Extraction (Poaching) of Biological Resources in the Caspian Sea. The authors propose recommendations on the development of this cooperation and the application of the experience of countries with a common history of criminal law development, but different approaches to the implementation of the goal of protecting aquatic biological resources.